(untitled) (Revista de Ciências Agroveterinárias, 2014)
Currently there are several commercial products based on amino acids and phosphite recommended for foliar fertilization; however, despite the relevance of this issue, there are few literature studies on their use on rice crops. Therefore, the objective of this research was to evaluate the agronomic and economic effi ciency of amino acid applications on the irrigated rice crop (Oryza sativa L.). The experiments were performed under field conditions in Rio Grande, RS using the IRGA 424 cultivar and in Cidreira, RS with the Puitá INTA CL cultivar. The experimental design at both locations was a randomized block design with four replications. The treatments consisted of different combinations of the products Ajifol Fosfito Plus®, Ajifol®, Amino Plus® and trifloxystrobin + tebuconazole fungicide over three periods of application. Each portion consisted of 18 lines of rice plants of 7 m in length, spaced 0.17 m apart. The following parameters were evaluated: control of brown spot on leaves and panicles in two seasons, spikelet number, number of filled grains, spikelet sterility percentage, 1,000 grains weight and yield. It can be concluded that the use of products based on amino acids + phosphite applied in flowering and milky grain stages regulates the infection of Bipolaris oryzae in a similar way to the isolated application of trifloxystrobin + tebuconazole fungicide in the same phases. The amino acids + phosphite application in flowering and milky grain stages associated to the application of the trifloxystrobin + tebuconazole fungicide provide an increase in grain yield and in the profit margin of irrigated rice.